A novel discussion on centripetal force - Bhattacharjee,Pramode Ranjan (2019)
Abstract In order to enrich the field of Newtonian mechanics, some novel approaches for the derivation of the expression for the centripetal force have been offered in this paper. The paper starts with a lucid and easily readable discussion of how the centripetal force arises when a particle undergoes uniform circular motion and it ends with a systematic presentation of four analytical novel schemes in regard to the derivation of the expression for the centripetal force.